Traditional herbal medicine for the prevention of chemotherapy-induced peripheral neuropathy: a systematic review and meta-analysis with association rule analysis - Kim, Eun Hye; Jin, Hayun; Lee, Su Hyeon; Yoon, Seong Woo (Frontiers in Pharmacology, 2025)
Introduction: This systematic review and meta-analysis evaluated the preventive efficacy and safety of orally-administered traditional herbal medicine (THM) for the management of chemotherapy-induced peripheral neuropathy (CIPN) in patients with cancer.Methods:Randomized controlled trials (RCTs) evaluating the efficacy of orally-administered THM in the prevention of CIPN published up to 30 April 2024 were retrieved from nine databases. The primary outcome was the incidence of CIPN, and the secondary outcomes included changes in neuropathic pain intensity, nerve conduction study parameters, Karnofsky Performance Scale (KPS) scores, and the incidence of adverse events. The quality of the studies and the strength of the evidence were evaluated using the Cochrane Risk of Bias Assessment Tool and Grading of Recommendations Assessment, Development, and Evaluation (GRADE) method. Key herbal combinations were identified by conducting an association rule analysis.Results:Thirty-seven RCTs involving 2,882 patients were included. Significant differences were observed between THM and the placebo [RR 0.83, 95% CI 0.74–0.93, p < 0.05; low quality of evidence], usual care [RR 0.51, 95% CI 0.37–0.69, p < 0.05; moderate quality of evidence], and no treatment [RR 0.62, 95% CI 0.54–0.71, p < 0.05; moderate quality of evidence] in terms of in the incidence rate of CIPN. A significant reduction in the intensity of neuropathic pain [SMD -0.81, 95% CI -1.07 to −0.56, p < 0.05; high quality of evidence] and a significant improvement in KPS [MD 8.18, p < 0.05; low quality of evidence] were observed in the THM compared to no treatment. Furthermore, compared with usual care and no treatment, the use of THM yielded a significant improvement in the nerve conduction parameters with low quality of evidence. No serious adverse events were reported. The combination of Astragali Radix and Cinnamomi Ramulus as the strongest herbal combination used for the prevention of CIPN.Conclusion:THM may be a promising option for the prevention of CIPN in patients with cancer. Low certainty of evidence, and substantial heterogeneity and risk of bias can limit the strength of the conclusions. Further well-designed and rigorously reported randomized controlled trials are warranted to confirm these findings and clarify their clinical applicability.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero, Identifier: CRD42021270942.